2018
DOI: 10.1038/s41386-018-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

TSPO upregulation in bipolar disorder and concomitant downregulation of mitophagic proteins and NLRP3 inflammasome activation

Abstract: Bipolar disorder (BD) is a chronic, debilitating illness with a global prevalence of up to 4.8%. The importance of understanding how dysfunctional mitochondria and mitophagy contribute to cell survival and death in BD is becoming increasingly apparent. Therefore, the purpose of this study was to evaluate the mitophagic pathway and NLRP3 inflammasome activation in peripheral blood mononuclear cells (PBMCs) of patients with BD and healthy individuals. Since 18-kDa translocator protein (TSPO) plays an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 75 publications
0
51
0
Order By: Relevance
“…The proteins included were those of the electron transport chain (ETC)-complex I subunits (NDUFV1, NDUFV2, NDUFS1), complex II subunit SDHA and complex IV subunit COX2; apoptosis-BAX, Bcl-2, CASP3, mitochondrial fission/fusion-OPA1, MFN1, Drp1, FIS1 and autophagy-Beclin1, p62. Most of the included proteins were reported abnormal in one or both disorders [31][32][33][34][35][36][37][38] . By comparing mitochondrial parameters with and without drug treatment, a specific profile of the effect of each of the drugs was obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins included were those of the electron transport chain (ETC)-complex I subunits (NDUFV1, NDUFV2, NDUFS1), complex II subunit SDHA and complex IV subunit COX2; apoptosis-BAX, Bcl-2, CASP3, mitochondrial fission/fusion-OPA1, MFN1, Drp1, FIS1 and autophagy-Beclin1, p62. Most of the included proteins were reported abnormal in one or both disorders [31][32][33][34][35][36][37][38] . By comparing mitochondrial parameters with and without drug treatment, a specific profile of the effect of each of the drugs was obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…146 By drawing on the concept of mitochondrial quality control, recent studies have demonstrated that patients with BD present an imbalance in mitochondrial fission and fusion toward fission, followed by a decrease in the levels of mitophagy proteins and increase in caspase-3 protein levels in peripheral blood mononuclear cells, suggesting that, in patients with BD, the number of damaged mitochondria exceeds the capacity of mitophagy, and apoptosis becomes the dominant pathway to minimize tissue damage. 147,148 Moreover, numerous studies have provided evidence of increased ROS production and oxidative stress in patients with BD. Replicated evidence has documented alterations in multiple aspects of oxidative stress regulation, including the production of ROS and reduced antioxidant capacity.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“… 146 By drawing on the concept of mitochondrial quality control, recent studies have demonstrated that patients with BD present an imbalance in mitochondrial fission and fusion toward fission, followed by a decrease in the levels of mitophagy proteins and increase in caspase-3 protein levels in peripheral blood mononuclear cells, suggesting that, in patients with BD, the number of damaged mitochondria exceeds the capacity of mitophagy, and apoptosis becomes the dominant pathway to minimize tissue damage. 147 , 148 …”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…It has also been shown that in peripheral mononuclear cells (PBMCs) of bipolar disorder (BD) patients, both TSPO and VDAC mRNA and protein expression levels were highly increased, relative to their levels in healthy controls [106]. Moreover, the ratio of TSPO to VDAC was greater in BD than that in healthy controls [106].…”
Section: The Relationship Between Tspo and Vdac1 Expressionmentioning
confidence: 99%
“…It has also been shown that in peripheral mononuclear cells (PBMCs) of bipolar disorder (BD) patients, both TSPO and VDAC mRNA and protein expression levels were highly increased, relative to their levels in healthy controls [106]. Moreover, the ratio of TSPO to VDAC was greater in BD than that in healthy controls [106]. In addition, it has been shown that the increase in mitochondrial ROS induced by an increase in the TSPO:VDAC1 ratio may activate protein kinase-Cε (PKCε) through the Raf-1-MEK1/2-ERK1/2 pathway, promoting the expression of TSPO [107].…”
Section: The Relationship Between Tspo and Vdac1 Expressionmentioning
confidence: 99%